Effects of genetic components of plant development on yield-related traits in wheat (Triticum aestivum L.) under stress-free conditions - Horváth, Ádám; Kiss, Tibor; Berki, Zita; Horváth, Ádám D.; Balla, Krisztina; Cseh, András; Veisz, Ottó; Karsai, Ildikó (Frontiers in Plant Science, 2023)
The dynamics of plant development does not only impact ecological adaptation, but it also contributes to the realisation of genetically determined yield potentials in various environments. Dissecting the genetic determinants of plant development becomes urgent due to the global climate change, which can seriously affect and even disrupt the locally adapted developmental patterns. In order to determine the role plant developmental loci played in local adaptation and in yield formation, a panel of 188 winter and facultative wheat cultivars from diverse geographic locations were characterised with the 15K Illumina SNP chip and functional markers of several plant developmental genes and included into a multi-season field experiment. Genome wide association (GWA) analyses were conducted on five consecutive developmental phases spanning from first node appearance to full heading together with various grain yield related parameters. The panel was balanced for the PPD-D1 photoperiod response gene, which facilitated the analyses in the two subsets of photoperiod insensitive and sensitive genotypes in addition to the complete panel. PPD-D1 was the single highest source, explaining 12.1 - 19.0% of the phenotypic variation in the successive developmental phases. In addition, 21 minor developmental loci were identified, each one explaining only small portions of the variance, but together their effects amounted to 16.6 – 50.6% of phenotypic variance. Eight loci (2A_27, 2A_727, 4A_570, 5B_315, 5B_520, 6A_26, 7A_1-(VRN-A3), and 7B_732) were independent of PPD-D1. Seven loci were only detectable in the PPD-D1 insensitive genetic background (1A_539, 1B_487, 2D_649, 4A_9, 5A_584-(VRN-A1), 5B_571-(VRN-B1), and 7B_3-(VRN-B3)), and six loci were only detectable in the sensitive background, specifically (2A_740, 2D_25, 3A_579, 3B_414, 7A_218, 7A_689, and 7B_538). The combination of PPD-D1 insensitivity and sensitivity with the extremities of early or late alleles in the corresponding minor developmental loci resulted in significantly altered and distinct plant developmental patterns with detectable outcomes on some yield-related traits. This study examines the possible significance of the above results in ecological adaptation.